PENGARUH KESADARAN MEREK DAN CITRA MEREK TERHADAP NIAT BELI PADA KONSUMEN HERBALIFE DI SURABAYA - Terrius Purnomo (Agora, 2018)
The purchase intention of Herbalife products in this research is influenced by brand awareness and consumer brand image. The aims of this study is to determine the effect on: (a) Brand awareness toward purchase intention, (b) Brand image toward purchase intention, and (c) Brand awareness and brand image toward purchase intention on Herbalife Consumers in Surabaya. This type of research includes explanatory research with quantitative approach. The sample in this research is 110 consumers of Herbalife product in Surabaya with sampling technique that is purposive sampling. Technique of data collection is done through quetionnairers. Analysis data of this research using multiple linear regression. The results of this study indicate that: (a) Brand awareness significantly influences purchase intentions, (b) Brand image significantly influence purchase intentions, and (c) Brand awareness and brand image together significantly influence purchase intentions on Herbalife consumers in Surabaya.